Research on the Impact of China’s Population Aging on Economic Development - Zheng, Caizhe (Transactions on Economics, Business and Management Research, 2023)
China has entered an aging society, and population aging has a different impact on the economy, this paper studies the characteristics of China’s population aging, and the causes of aging, this paper expounds on the population aging on consumption, savings, labor, technology, etc. The impact of economic factors, and put forward from the Angle of social welfare and pension industry development strategy to promote the development of the economy.